Legal Liability of Military Doctors for Medical Malpractice within the In-donesian Legal System - Tresna, I Komang (Law and Economics, 2026)
Medical services provided by military doctors have distinctive characteristics due to their position under both health law and military law regimes. This dual legal framework raises specific legal issues when allegations of medical malpractice occur, particularly concerning the legal liability of military doctors. This study seeks to examine the legal accountability of military physicians for medical negligence within the Indonesian legal framework. This study utilizes a normative legal methodology incorporating legislative, conceptual, and case analyses. The legal resources comprise primary, secondary, and tertiary legal sources. The results demonstrate that military physicians are governed by national health legislation while adhering to the specific stipulations of military law. The legal accountability of military physicians for medical misconduct may manifest as criminal, civil, and administrative culpability, enforced through legal frameworks that ensure legal certainty, justice, and patient safeguarding. This research advances health law and the enforcement of legal accountability for military medical professionals in Indonesia